2009
DOI: 10.1124/mol.109.056101
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Secretagogues and Growth Hormone Releasing Peptides Act As Orthosteric Super-Agonists but Not Allosteric Regulators for Activation of the G Protein Gαo1 by the Ghrelin Receptor

Abstract: Some growth hormone secretagogues act as agonists at the ghrelin receptor and have been described as "ago-allosteric" ligands because of an ability to also modulate the maximum efficacy and potency of ghrelin (Holst et al., 2005). In membranes prepared from cells coexpressing the human ghrelin receptor and, growth hormone-releasing peptide 6 (GHRP-6), and the 2(R)-hydroxypropyl derivative of 3-amino-3-methyl-N-(2,3,4,5-tetrahydro-2-oxo- -692,585) each functioned as direct agonists, and each displayed higher ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 41 publications
2
34
0
4
Order By: Relevance
“…We took advantage here of G protein activation BRET biosensors (31,32) that directly report on the conformational change of G protein upon activation, to assess whether the partial agonist behavior of these ligands toward IP1 production resulted from their G q partial agonism. Although it was reported that GHSR1a activated G protein-dependent signaling pathways through G q , G i , G o (23,30,50), and G 13 (51), these conclusions were drawn from studies that indirectly measured G protein activation. We monitored here the selective coupling of GHS-R1a to the G protein family using activation biosensors for a panel of G protein subtypes and isoforms (G q , G i1 , G i2 , G i3 , G oa , G ob , G s , G 12 , and G 13 ).…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…We took advantage here of G protein activation BRET biosensors (31,32) that directly report on the conformational change of G protein upon activation, to assess whether the partial agonist behavior of these ligands toward IP1 production resulted from their G q partial agonism. Although it was reported that GHSR1a activated G protein-dependent signaling pathways through G q , G i , G o (23,30,50), and G 13 (51), these conclusions were drawn from studies that indirectly measured G protein activation. We monitored here the selective coupling of GHS-R1a to the G protein family using activation biosensors for a panel of G protein subtypes and isoforms (G q , G i1 , G i2 , G i3 , G oa , G ob , G s , G 12 , and G 13 ).…”
Section: Discussionmentioning
confidence: 98%
“…D, G 12 activation by the thromboxane A 2 ␣ type (TP␣) receptor: HEK293T cells co-expressing the TP␣ receptor and G 12 biosensor were stimulated by 10 Ϫ6 M U46619, and the BRET signal was recorded at described in A. 50 and E max are reported in Table 2. tin2 recruitment, and ERK1/2 phosphorylation. We took advantage here of G protein activation BRET biosensors (31,32) that directly report on the conformational change of G protein upon activation, to assess whether the partial agonist behavior of these ligands toward IP1 production resulted from their G q partial agonism.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations